2005
DOI: 10.1038/sj.bjc.6602890
|View full text |Cite
|
Sign up to set email alerts
|

Dairy consumption and ovarian cancer risk in the Netherlands Cohort Study on Diet and Cancer

Abstract: Ovary cancer risk in relation to consumption of dairy products was investigated using a self-administered questionnaire on dietary habits and other risk factors for cancer, which was completed in 1986 by 62 573 postmenopausal women participating in the Netherlands Cohort Study. Follow-up for cancer was implemented by annual record linkage with the Netherlands Cancer Registry and a nationwide pathology registry. After 11.3 years of follow-up, data of 252 incident epithelial ovarian cancer cases and 2216 subcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…It should be noted that in the Nurses' Health Study (65) and the Swedish Mammography Cohort (66), lactose consumption was associated with increased risk of serous ovarian cancer, but not with other subtypes, suggesting that future studies should consider histologic type when evaluating this association. In contrast, a report from the Netherlands Cohort Study of Diet and Cancer (67) reported no association with any dairy products or lactose and epithelial ovarian cancer or the serous subtype. Furthermore, there was no indication of an association with milk/dairy product or calcium consumption in a recent study pooling data from 12 cohort studies (68) and only a weak association with lactose intake at a level equivalent to 3 or more glasses of milk per day (RR = 1.19; 95% CI = 1.01-1.40 comparing ≥30 g/day vs. <10 g/day).…”
Section: Red Meat Fish Eggsmentioning
confidence: 69%
“…It should be noted that in the Nurses' Health Study (65) and the Swedish Mammography Cohort (66), lactose consumption was associated with increased risk of serous ovarian cancer, but not with other subtypes, suggesting that future studies should consider histologic type when evaluating this association. In contrast, a report from the Netherlands Cohort Study of Diet and Cancer (67) reported no association with any dairy products or lactose and epithelial ovarian cancer or the serous subtype. Furthermore, there was no indication of an association with milk/dairy product or calcium consumption in a recent study pooling data from 12 cohort studies (68) and only a weak association with lactose intake at a level equivalent to 3 or more glasses of milk per day (RR = 1.19; 95% CI = 1.01-1.40 comparing ≥30 g/day vs. <10 g/day).…”
Section: Red Meat Fish Eggsmentioning
confidence: 69%
“…The European Prospective Investigation of Cancer (EPIC) and the Swedish Mammography Study specifically evaluated the relationship between red meat intake and ovarian cancer risk and found no significant association (12),(31). Alternately, four studies evaluated dairy intake (a source of animal fat) in relation to risk; three found no significant association (12),(20),(32) while the study by Larsson et al, showed a 60% greater risk for invasive ovarian cancer in relation to dairy intake (33) an association that seemed to be largely attributed to milk and cheese, but not yogurt intake. The increased risk associated with dairy and specifically lactose intake was shown in the Nurses’ Health Study cohort, but risk was limited to the subgroup of women diagnosed with a serous tumor subtype, accounting for a 2-fold higher risk (RR 2.07, 95% CI, 1.27–3.40) (34).…”
Section: Resultsmentioning
confidence: 99%
“…An association between ovarian cancer risk and a high whole milk intake, but not low-fat dairy product intake, suggested that fat, and not galactose, was the component that increases the cancer risk (133) . Contrarily, a cohort study on diet and cancer carried out in The Netherlands (134) did not find an association between dairy products or lactose intake and ovarian cancer risk. A modest increase in the risk of ovarian cancer with lactose intake at the level of three or more glasses of milk per d was observed in a pooled analysis of twelve cohort studies (135) .…”
Section: Relationship Between Dietary Ca 21 and Lipid Metabolismmentioning
confidence: 99%